Zoom: Sebastião Salgado: The Amazon laid bare - Katerina Markelova (The UNESCO Courier, 2022)
Skies filled with inky clouds, forest-dwellers captured in the intimacy of their daily lives, mountains emerging from the vegetation. The Amazon that Sebastião Salgado shows us is not one of clichés – all luxuriance and vivid colours, with variations of bright green foliage, purple earth, and rivers irrigating the forest. On the contrary, Salgado’s images portray a world in chiaroscuro, grandiose, complex. Fragile too.